2017
DOI: 10.1038/srep43353
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of Metabolomics and Transcriptomics in Cervical Cancer

Abstract: Cervical cancer (CC) still remains a common and deadly malignancy among females in developing countries. More accurate and reliable diagnostic methods/biomarkers should be discovered. In this study, we performed a comprehensive analysis of metabolomics (285 samples) and transcriptomics (52 samples) on the potential diagnostic implication and metabolic characteristic description in cervical cancer. Sixty-two metabolites were different between CC and normal controls (NOR), in which 5 metabolites (bilirubin, Lyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 63 publications
2
69
0
Order By: Relevance
“…Based on the multi-OMICS data integration, a prediction model, developed and validated against a large cohort of breast cancer patients, showed several cancer-related metabolites; namely, glucose, Glycine, serine, and acetate are significantly associated with patient survival [ 55 ]. A similar OMICS integration approach including metabolomics and transcriptomics was applied to identify potential diagnostic and prognostic cancer biomarkers for prostate [ 56 ] and cervical cancers [ 57 ]. Ren et al identified the accumulation of certain metabolites such as S-adenosylhomoserine (SAH), 5-methylthioadensine (MTA), and S-adenosylmethionine (SAM) in prostate cancer compared to noncancerous tissues [ 56 ].…”
Section: Application Of Multi-omics Approach: Success Stories So Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on the multi-OMICS data integration, a prediction model, developed and validated against a large cohort of breast cancer patients, showed several cancer-related metabolites; namely, glucose, Glycine, serine, and acetate are significantly associated with patient survival [ 55 ]. A similar OMICS integration approach including metabolomics and transcriptomics was applied to identify potential diagnostic and prognostic cancer biomarkers for prostate [ 56 ] and cervical cancers [ 57 ]. Ren et al identified the accumulation of certain metabolites such as S-adenosylhomoserine (SAH), 5-methylthioadensine (MTA), and S-adenosylmethionine (SAM) in prostate cancer compared to noncancerous tissues [ 56 ].…”
Section: Application Of Multi-omics Approach: Success Stories So Fmentioning
confidence: 99%
“…Elevated expression of Glycine N-methyltransferase ( GNMT ) evident from transcriptomics analysis was assumed to be responsible for the induction of SAH and was proposed as a tumor-susceptibility gene in prostate cancer [ 56 ]. On the other hand, Yang et al identified five metabolites, bilirubin, LysoPC(17:0), n-oleoyl threonine, 12-hydroxydodecanoic acid, and tetracosahexaenoic acid, as candidate biomarkers for cervical cancers [ 57 ]. Integration strategy leads to the reconstruction of an interconnected gene-metabolic network where seven biochemical pathways were used to identify five candidate metabolite biomarkers [ 57 ].…”
Section: Application Of Multi-omics Approach: Success Stories So Fmentioning
confidence: 99%
See 1 more Smart Citation
“…As the most common female cancer, breast cancer has been extensively studied [10][11][12][13][14][15][16][17], also providing untapped opportunities in metabolomics studies in association with gynecological cancers. Moreover, biomarkers have been proposed for application in cervical and ovarian cancers based on metabolomics [18][19][20][21][22][23][24][25].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study found serum metabolites contributing to discriminations between cervical cancer, cervical intraepithelial neoplasia, and chronic cervicitis (Ye et al, 2015 ). There is an investigation showed biomarkers for cervical cancer diagnosis and screening based on metabolomics and transcriptomics (Yang et al, 2017 ). However, what is the pathogenesis of cervicitis and what is the diagnostic biomarker between health and cervicitis patients?…”
Section: Introductionmentioning
confidence: 99%